ChemInform Abstract: Two New Pyrrolidine Alkaloids, Codonopsinol C (Ia) and Codonopiloside A (Ib), Isolated from Codonopsis pilosula. Issue 24 (2nd June 2014) - Wakana, Daigo; Kawahara, Nobuo; Goda, Yukihiro
Abstract isolation and structural elucidation